(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2021)
Introduction: Poly-orchidism is a rare congenital anomaly with less than 100 cases reported in the world literature. As many theories have an etiology regarding poly-orchidism but still exact etiology is not clear. But majority patient presents with painless scrotal/groin swelling. In rare presentation it may present with an indirect hernia, varicocele, hydrocele, epididymitis, mal-descended testis. The majority have tri-orchidism and the supernumerary testis is most frequently found on the left side. Aims: This is a study of rare case report of tri-orchidism of 3 yr. male child present with absent left side testis. On exploration found that two testes were with the vas having distally 2 limbs draining both testis in the ’Y’ fashion. Result: In case of this tri-orchidism ideally plan of management is various. If investigation vise testis found atrophied or non-functional then plan of management should be orchidectomy. In this case as clinically both the testis appeared normal both the testis was placed in the left scrotum and orchidopexy was done Conclusion: Poly-orchidism may be a rare genitourinary abnormality and its management is still controversial. The management will depend upon the location, size and anatomical organization of the testicular drainage system and the age of the patient.